Pengaruh Model Pembelajaran Kooperatif Tipe Numbered Heads Together Terhadap Pemahaman Konsep Matematika Peserta Didik Kelas VIII SMPN 3 Pariaman - YUTRI ZAIRAWATI . (Jurnal Edukasi dan Penelitian Matematika, 2019)
Understanding of mathematical concepts is one of the purpose in mathematics learning. Understanding of mathematical concepts is the foundation for students to understand mathematics. But in fact, Understanding of mathematical concepts of students at grade VIII SMPN 3 Pariaman was low. It is caused by learning model that used has not facilitated students to develop their Understanding of mathematical concepts. One effort to overcome this problem is by applying Numbered Heads Together of Cooperative Learning. This learning model helps students to develop their Understanding of mathematical concepts. The type of research is a quasi-experimental design with Static Group Design. The research hypothesis is carried out by using the t-test. These results indicate that the students understanding mathematical concepts in learning that apply the model NHT is better than the students understanding mathematical concepts in learning that apply conventional learning.Keywords – Understanding of mathematical concepts, Numbered Heads Together, Conventional Learning